Two-week, high-dose proton pump inhibitor, moxifloxacin triple Helicobacter pylori therapy after failure of standard triple or non-bismuth quadruple treatments. Issue 2 (February 2015) - Gisbert, Javier P.; Romano, Marco; Molina-Infante, Javier; Lucendo, Alfredo J.; Medina, Enrique; Modolell, Inés; Rodríguez-Tellez, Manuel; Gomez, Blas; Barrio, Jesús; Perona, Monica; Ortuño, Juan; Ariño, Inés; et al.
Abstract Background Aim was to evaluate the efficacy and tolerability of a moxifloxacin-containing second-line triple regimen in patients whose previous Helicobacter pylori eradication treatment failed. Methods Prospective multicentre study including patients in whom a triple therapy or a non-bismuth-quadruple-therapy failed. Moxifloxacin (400 mg qd), amoxicillin (1 g bid), and esomeprazole (40 mg bid) were prescribed for 14 days. Eradication was confirmed by 13C-urea-breath-test. Compliance was determined through questioning and recovery of empty medication envelopes. Results 250 patients were consecutively included (mean age 48 ± 15 years, 11% with ulcer). Previous (failed) therapy included: standard triple (n = 179), sequential (n = 27), and concomitant (n = 44); 97% of patients took all medications, 4 were lost to follow-up. Intention-to-treat and per-protocol eradication rates were 82.4% (95% CI, 77–87%) and 85.7% (95% CI, 81–90%). Cure rates were similar independently of diagnosis (ulcer, 77%; dyspepsia, 82%) and previous treatment (standard triple, 83%; sequential, 89%; concomitant, 77%). At multivariate analysis, only age was associated with eradication (OR = 0.957; 95% CI, 0.933–0.981). Adverse events were reported in 25.2% of patients: diarrhoea (9.6%), abdominal pain (9.6%), and nausea (9.2%). Conclusion 14-day moxifloxacin-containing triple therapy is an effective and safe second-line strategy in patients whose previous standard triple therapy or non-bismuth quadruple (sequential or concomitant) therapy has failed, providing a simple alternative to bismuth quadruple regimen.